The Effect of Annual Report Readability, Carbon Emission Disclosure and Green Accounting Practices on Company Value - Anggita, Wenni; Nugroho, Ari Agung; Suhaidar, Suhaidar (Universitas Bangka Belitung, 2024)
This study aims to analyze the effect of annual report readability, carbon emission disclosure and green accounting practices on company value with the research object of manufacturing companies listed on the IDX in 2020-2022. The approach used in this study is a descriptive quantitative using multiple linear regression. The sample of this study were 38 mining companies with an observation period of 3 years resulting in 114 research data. Data testing was carried out by partial analysis using the eviews tool. The results of this study found that the annual report readability, carbon emission disclosure and green accounting practices had a positive and significant effect on company value. This indicates that the easier an annual report is to read, the higher the quality of information received by its users, especially stakeholders, so that it greatly influences the decision making of investors. In addition, green accounting practices and carbon emissions disclosure is the first step that companies can take to minimize environmental problems faced by companies. This research is different from previous research, this study tries to combine how easy it is to read financial statements and also how environmental accounting and carbon emissions disclosure by companies can increase company value.